The politics of magnate power in England and Wales, 1389-1413 - Dunn, Alastair (Oxford historical monographs., 2003)
Using previously neglected sources, this work offers a radical reinterpretation of the Lancastrian revolution, and the establishment of Henry IV's kingship. It also re-examines the reign of Richard II, and charts the shift of power between the crown and the nobility at the turn of the fifteenth century.